Answer:
Step-by-step explanation:
The two acute angles add up to 90 degrees. That's because every triangle has 180 degrees and a right angle is 90 degrees.
<m1 + <m2 + 90 = 180 Subtract 90 from both sides.
<m1 + <m2 + 90 - 90 = 180 - 90 Combine
<m1 + <m2 = 90
Let m1 = 9*m2 Substitute.
9m2 + m2 = 90 Combine
10 m2 = 90 Divide by 10
10m2/10 = 90/10
m2 = 9
m1 = 9*m2
m1 = 9 * 9
m1 = 81
The right angle = 90
m1 = 81
m2 = 9
Answer:
Step-by-step explanation:
1. A boutique is offering a 15% discount on a dress. Calculate the cash price for the dress if the marked price is $2300.
2. An artist charges $980 for a portrait but gives a 5% discount. Calculate the cash price of the portrait.
3. A television set has a selling price of $1950. A 10% discount is offered for cash. What amount is the cash price to the customer?
4. A store is having a sale on dining sets. The marked price is $47,320, however a discount of 12% is being offered for cash. Calculate the cash price of the dining set.
5. A tailor charges $2487 for a suit but gives a discount of 5%. What is the cash price for the suit?
6. A washing machine has a marked price of $33,000 and a discount of 6% is given for cash. What is the cash price of the washing machine?
7. Laura sees a summer dress in a store with a marked price of $1303. A discount of 9% is given on cash. What is the cash price of the summer dress?
Light behaves mainly like a wave but it can also be considered to consist of tiny packages of energy called photons. Photons carry a fixed amount of energy but have no mass. They also found that increasing the intensity of light increased the number of electrons ejected, but not their speed.
Answer:
3(a - b)(a + b)
Step-by-step explanation:
Factorize: (2a - b)² - (a - 2b)²
- Different of Perfect a Square rule: a² - b² = (a + b)(a - b)
(2a - b)² - (a - 2b)² = [(2a - b) + (a - 2b)] × [(2a - b) - (a - 2b)]
1. Distribute and Simplify:
Distribute the (+) sign on the first bracket and simplify: [(2a - b) + (a - 2b)] → 2a - b + a - 2b → (3a - 3b)
Distribute the (-) sign on the first bracket and simplify: [(2a - b) - (a - 2b)] → 2a - b – a + 2b → (a + b)
We now have:
(3a - 3b)(a + b)
2. Factor out the Greatest Common Factor (3) from 3a - 3b:
(3a - 3b) → 3(a - b)
3. Add "(a + b)" back into your factored expression:
3(a - b)(a + b)
Hope this helps!
Answer:
no
Step-by-step explanation:
because pa puts in more money making his rate higher
Answer: 3
Step by step explanation